Penerapan Terapi Rendam Kaki Air Jahe Merah Hangat Pada Lansia Penderita Hipertensi Di RSUD dr. Soeratno Gemolong - Alfita Diah Safitri; Tri Susilowati; Fitria Purnamawati (Jurnal Ventilator, 2023)
Background: Hypertension or high blood pressure is when the systolic pressure is more than 140 mmHg and the diastolic blood pressure is more than 90 mmHg. WHO data (2015) shows that around 1.13 billion people in the world have hypertension. The number of people with hypertension continues to increase every year, it is estimated that every year 20.44 million people die from hypertension and its complications. Non-pharmacological management to lower blood pressure can be done independently and naturally, namely foot hydrotherapy (warm foot bath). Foot soaks can be combined with other herbal ingredients, one of which is ginger. Objective: To determine the effect of soaking feet with warm ginger water in lowering blood pressure in hypertensive patients. Method: The application was carried out using a descriptive method in the form of a case study to 2 respondents with hypertension in the form of a pretest-posttest. The application is carried out within two days for 15 minutes by sitting on a bed or chair and then soaking the feet in a basin containing warm red ginger water with a water temperature of 37°C. Findings: Based on the results of the application of warm red ginger water foot soak therapy is decrease in blood pressure in elderly patients with hypertension, namely 160/100 mmhg and 150/100 mmhg. Implications: warm red ginger water foot soak therapy can be used as a non-pharmacological technique or independent intervention in elderly patients with hypertension